The Territorial Community Budget as a Basis of Local Finances - Koroviy Valeriy V. (Bìznes Inform, 2018)
The article is aimed at disclosing the essence and role of budgets of territorial communities in the system of financial provision of the local self-government, defining the approaches to formation of local budgets as a weighty instrument of the socio-economic development of territories. Achieving the financial self-sufficiency of local government will allow implementing of the principle of balanced functioning of local finances. An important task is to determine the role of the institution of local finances in the modern economic environment, the need to introduce institutional changes in the budget process, the carrying out of administrative-territorial transformations. The inter-budgetary transfers and budget expenditures play a decisive role in increasing the volume of financing of social programs, ensuring financial stability, and strengthening its influence on the socio-economic development of territory along with balance of the local budget. It is expedient to increase the innovation component of local budgets, the volume of financing of social programs, decrease dependence of local budgets on transfers from the State budget, ensuring economic and financial stability, strengthening the influence of regulation of the inter-budgetary relations on the socio-economic development of territories.